2015
DOI: 10.18311/sdmimd/2015/3962
|View full text |Cite
|
Sign up to set email alerts
|

Management of Gen Y Employees Through Psychological Contract - 'An Exploratory Study in IT/ITES Companies'

Abstract: Abstract:Globalization has led to diverse workforce for most of the multinational corporations. Today's workforce is highly diverse based on Gender, Race, Ethnicity, Nationality, Age, Physical capabilities at a surface level and values, attitudes, personality, education and religion at a deeper level.Diversity Management means valuing the differences in people. In India, Diversity mostly referred to gender related initiatives in the past. But today companies are moving to include national culture, age, physica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…An exploratory study by Pant and Venkateswaran (2015) of Gen Y revealed important workplace expectations using the lens of PC. Employees with disability have unique workplace expectations such as job designation and training on communication skills when compared with other employee groups like women.…”
Section: Hypotheses Formulationmentioning
confidence: 99%
“…An exploratory study by Pant and Venkateswaran (2015) of Gen Y revealed important workplace expectations using the lens of PC. Employees with disability have unique workplace expectations such as job designation and training on communication skills when compared with other employee groups like women.…”
Section: Hypotheses Formulationmentioning
confidence: 99%
“…It is referred here to populations from urban, rural, remote and isolated areas. In the case of these populations, various issues need to be taken into consideration: access to the university, access to professions and, consequently, the training of professionals in regional realities, the return of graduates to the regions and the ongoing training of professionals established in the region (Pant & Vijaya, 2015).…”
Section: Geographic Diversitymentioning
confidence: 99%